PRODUCTIVITY TECHNIQUES, COMPETITIVENESS AND WEALTHNESS: EVIDENCE FROM COMMUNITY ENTERPRISE IN SAKON NAKHON - Intarapanich, Supawita; Pakpian, Thanya; Limpsurapong, Chattawat (RMUTT Global Business and Economics Review, 2022)
This study aims to 1) To investigate the impacts of productivity techniques on operational capability. 2) To investigate the impacts of productivity techniques on competitive capability. 3) To investigate the impacts of operational capability on competitiveness. 4) To investigate the impacts of operational capability on wealthness. 5) To investigate the impacts of competitiveness on wealthness. Data were collected from 400 community enterprises in Sakon Nakhon province, using simple random sampling to gather data. Questionnaire is used to collected data. And multiple regression is used to analyze all hypotheses. The results found that productivity techniques including technology focus, employee focus, product focus, job improvement, and inventory management focus have positive relate on operational capability. Accordingly, group participation focus, employee focus, product focus, job improvement, and inventory management focus have positive relate on competitiveness. On the other hand, the operational capability such as mass customization capability, exploitative innovation capability, and exploratory innovation capability have positive relate on competitiveness. Whereas exploitative innovation capability, and exploratory innovation capability have positive relate on wealthness. The competitiveness, including change capability, reciprocal engagement-based capability, trust-based capability, and influence-based capability have positive relate on wealthness.